Intersectionality and Social Drivers of Health in Cardiovascular Care - Madelyn Hurwitz; Jason Bonomo; Jared Spitz; Garima Sharma (Methodist DeBakey Cardiovascular Journal)
Social drivers of health (SDOH) are a significant contributor to persistent cardiovascular health disparities in the United States and globally. SDOH include psychosocial, environmental, socioeconomic, cultural, and governmental factors that impact health behaviors and outcomes. Multiple social drivers have been associated with trends in cardiovascular disease risk and health outcomes. These social drivers intersect in complex ways, and applying the concept of intersectionality is critical when considering ways to best address SDOH in cardiovascular care. Applying intersectionality, which considers the unique combination of social drivers associated with a community, allows for tailored interventions to address cardiovascular health disparities.